Subacute Toxicity Study of Leaf Extract of Saccharum officinarum - Edem, Utibe A; Okokon, Jude E (Biology, Medicine, & Natural Product Chemistry, 2025)
Saccharum officinarum (Family-Poaceae) is used traditionally to treat malaria and fever, among others. Evaluation of subacute administration ethanol leaf extract of Saccharum officinarum for possible effect on hematological indices, liver and kidney functions, and lipid profile of rats was carried out. The leaf extract (170, 340, 510 mg/kg body weight) was orally administered to male Wistar rats daily for 30 days, and the rats were sacrificed under light diethyl ether anesthesia after the administration. Subacute administration of S. officinarum leaf extract resulted in an insignificant increase in the body weights of rats without any significant (p>0.05) effect on the weights of liver and kidney when compared to control. The leaf extract treatment did not affect WBC, lymphocytes, monocytes, eosinophil, and basophil percentages. However, it caused significant (p<0.05) decreases in RBC and platelet counts, hemoglobin concentration, and PCV percentage, especially at the middle dose (374 mg/kg), and also prolonged bleeding and clotting time significantly (p<0.05) when compared to control.  The leaf extracts non-dose-dependently caused insignificant (p>0.05) decreases in total protein, albumin, and ALT levels. ALP was significantly (p<0.05) decreased at the highest dose (510 mg/kg). However, AST, total and conjugated bilirubin levels were significantly (p<0.01-0.001) decreased only at higher doses (340 and 510 mg/kg) of the extract. The leaf extract did not cause any significant (p>0.05) effect on urea, creatinine, potassium, and sodium as well as total cholesterol, triglyceride, VLDL, and LDL levels of rats, but the highest dose (510 mg/kg) significantly (p<0.05) increased Cl level and reduced HDL level of rats when compared to control.  The leaf extract exerts mild to moderate effects on the histology of the livers and kidneys of rats. Chronic study is advocated to investigate the effect of prolonged administration of rats’ extract organs and systems.